Lack of Association of SNPs from the FADS1-FADS2 Gene Cluster with Major Depression or Suicidal Behavior - Sublette, M. Elizabeth (Psychiatr Genet, 2016)
Fatty acid desaturase genes (FADS1-FADS2) encode for desaturases participating in biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFAs). Since LC-PUFAs are implicated in major depressive disorder (MDD) and suicide risk, and both are partly heritable, we studied the association of FADS1-FADS2 polymorphisms with MDD (635 cases, 480 controls), and suicide attempt status (291 attempters, 338 non-attempters).. Eighteen FADS-related single-nucleotide polymorphisms (SNPs) were genotyped from Caucasians enrolled in Madrid (n=791) or New York City (n=324), and entered as predictors into logistic regression analyses with diagnostic group or suicide attempt history as outcomes, and covariates location and sex. No associations were observed between any SNPs and diagnosis or attempt status. As statistical power was adequate, we conclude that FADS1-FADS2 genetic variants may not be a common determinant of MDD.